Use of schedule theory algorithms for task planning and time management tasks - М. Шматко; О. Жураковська (Adaptivni Sistemi Avtomatičnogo Upravlinnâ)
Good time management is a key factor in the success of work tasks and project management. In particular, scheduling tasks are an important part of workflow organization. An efficiently created schedule allows you to optimize time and resources, increasing the efficiency and quality of work performed. To solve scheduling problems, the theory of scheduling is used. At the moment, there are many algorithms for solving such tasks, but the algorithms must be customized to specific conditions, while ensuring the quality of the task and performance. In this article, we propose a hybrid algorithm that combines elements of evolutionary and greedy approaches to solve the problems of schedule theory.